2011 IEEE/ACM International Conference on Computer-Aided Design (ICCAD) 2011
DOI: 10.1109/iccad.2011.6105379
|View full text |Cite
|
Sign up to set email alerts
|

Fast analog layout prototyping for nanometer design migration

Abstract: This paper presents an analog layout migration methodology to quickly provide multiple layouts while keeping similar or better circuit performance. Unlike previous works that often generate a single layout that has exactly the same topology with the original layout, this new migration algorithm is able to provide results with different aspect ratios. First, various placement constraints, including topology, matching, and symmetry, are extracted from the original layout. The extracted constraints are hierarchic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Lai and Wong [26] further stated that the slicing trees can represent both slicing and non-slicing floorplans by integrating the compaction technique. Some other previous works [22,23] also showed that it is very efficient to apply the slicing-tree representation to design/layout migration and fixed-outline floorplanning. Therefore, it is desirable to explore analog placement using the slicing trees.…”
Section: Generation Of Symmetry Islands Using Slicing Treesmentioning
confidence: 93%
See 1 more Smart Citation
“…Lai and Wong [26] further stated that the slicing trees can represent both slicing and non-slicing floorplans by integrating the compaction technique. Some other previous works [22,23] also showed that it is very efficient to apply the slicing-tree representation to design/layout migration and fixed-outline floorplanning. Therefore, it is desirable to explore analog placement using the slicing trees.…”
Section: Generation Of Symmetry Islands Using Slicing Treesmentioning
confidence: 93%
“…• We augment the slicing-tree representation [21], which has been shown to be very efficient in design/layout migration [22] and fixed-outline floorplanning [23], to model the symmetryisland placement. To our best knowledge, none of the previous works presented any symmetric-feasible condition in the slicing trees.…”
Section: Our Contributionsmentioning
confidence: 99%
“…Previous works did not consider the required routing resource in the placement stage [8][9][10] or used an unfaithful congestion to adjust the generated placement [12][13][14]. To accurately predict the required routing resource during placement and generate nonstochastic placements, a routability-aware analog placement flow is proposed.…”
Section: Layout Templatementioning
confidence: 99%
“…In the literature, layout automation techniques for analog circuits are also a popular research direction [8][9][10][11][12][13][14]. In recent years, many researches [8][9][10] focus on studying the analog placement problem to consider the extra layout constraints such as matching, proximity, etc. The succeeding routing issue is often not considered due to the small number of nets in analog circuits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation